CYP35 family in Caenorhabditis elegans biological processes: fatty acid synthesis, xenobiotic metabolism, and stress responses - Sharoen Lim, Yu Ming; Mustafa, Alshagga; Cin, Kong; Mohammed Abdullah, Alshawsh; Salah Abdulrazak, Alshehade; Yan, Pan (Springer Nature, 2022)
With more than 80 cytochrome P450 (CYP) encoding genes found in the nematode Caenorhabditis elegans (C. elegans), the cyp35 genes are one of the important genes involved in many biological processes such as fatty acid synthesis and storage, xenobiotic stress response, dauer and eggshell formation, and xenobiotic metabolism. The C. elegans CYP35 subfamily consisted of A, B, C, and D, which have the closest homolog to human CYP2 family. C. elegans homologs could answer part of the hunt for human disease genes. This review aims to provide an overview of CYP35 in C. elegans and their human homologs, to explore the roles of CYP35 in various C. elegans biological processes, and how the genes of cyp35 upregulation or downregulation are influenced by biological processes, upon exposure to xenobiotics or changes in diet and environment. The C. elegans CYP35 gene expression could be upregulated by heavy metals, pesticides, anti-parasitic and anti-chemotherapeutic agents, polycyclic aromatic hydrocarbons (PAHs), nanoparticles, drugs, and organic chemical compounds. Among the cyp35 genes, cyp-35A2 is involved in most of the C. elegans biological processes regulation. Further venture of cyp35 genes, the closest homolog of CYP2 which is the largest family of human CYPs, may have the power to locate cyps gene targets, discovery of novel therapeutic strategies, and possibly a successful medical regime to combat obesity, cancers, and cyps gene-related diseases.